Hubungan Kebijakan Hutang, Insider Ownership dan Kebijakan Dividen dalam Mekanisme Pengawasan Masalah Agensi di Indonesia - D. Agus Harjito; Nurfauziah Nurfauziah (Jurnal Akuntansi dan Auditing Indonesia, 2006)
This study investigates the substitution relationship (substitutability) among debt policy, insider ownership, and dividend policy as the agency problem control mechanism in Indonesia. If the substitution relationship exists among the agency control mechanisms, the agency problem can be reduced through this relationship. Reducing the agency problem as a result can increase the firm value proxied by Tobin’s Q. This study employs 69 firms listed on Jakarta Stock Exchange from 2001 to 2004. The results of this study indicate that the substitutability among debt policy, insider ownership, and dividend policy as agency problem control mechanism does not exist effectively in Indonesia. Actually, there is substitutability relationship among the control mechanisms, but it is not effective. Keywords: Insider ownership, debt policy, dividend policy, agency problem, substitutability